Smart grid application in the Iraqi power system: current and future challenges - Saraa Ismaeel Khalel; Nagham Hikmat Aziz; Maha Abdulrhman Al-Flaiyeh (Institute of Advanced Engineering and Science, 2022)
A smart grid could generate and distribute electricity effectively economically, securely and sustainably. It offers customers more information and choice, including the export of energy to the grid, demand-side participation and energy efficiency. However, to implement a smart grid into the Iraqi power system, various challenges should be faced, especially concerns related to understanding the contents and features of this network compared with the traditional Iraqi network. As well as the challenges and risks of implementing the smart grid itself in the modern work environment, especially with the tremendous progress in communication technologies, which has brought serious problems to the operation of the network such as cyberattacks. Also, the traditional Iraqi network suffers from various problems, including the large deficit in the generated power-to-load demand ratio, which reaches about more than a third, and the great destruction that the network has been subjected to because of the wars that the country has been exposed to during the past three decades. In this study, a clear vision was presented to researchers and engineers who are interested in applying the smart grid in Iraq on this vital topic, which will greatly help in applying this essential matter to develop the work of the Iraqi power system and improve the efficiency and services it provides.